Guidelines for “Blue-Green” Urban Infrastructure: Adaptive Model and its Structural Elements - Ruban, Liudmyla (Landscape Architecture and Art, 2023)
An author’s methodological approach has been developed, based on the planning of a “blue-green” urban infrastructure for the conditions of a riverside city, as one of the possible ways to adapt settlements to climate change. An adaptive model of the “Blue-green” infrastructure of a riparian city is proposed, as well as a typology of its structural elements, purposes, and methods of application. This methodological approach develops certain provisions of the Sponge Cities practical urban planning strategy, applicable for versatile climatic conditions and successfully implemented since the 2000s in several Asian countries (Singapore, China, etc) and many European cities.